Analisis Dampak Permintaan Naiknya Upah Minimum Terhadap Perekonomian, Hukum Dan Kesejahteraan Nasional (Indonesian State Law Review (ISLRev), 2019)
The purpose of this article is to show the impact caused by the Minimum Wage on the National economy. approach used In avoiding the exploitation of labor in Indonesia, the government as the highest authority of the country, issues labor regulations. The regulation regulates the Minimum Wage that companies must pay to workers. The minimum wage is a safety device from the government to prevent the exploitation of Indonesian workers. However, many of the Indonesian workers are not aware that the application of the minimum wage is by the decent standard of living set by the government. They do a lot of prosecutions so that the minimum wage they get is always increasing. If analyzed, the demand for rising minimum wages will also harm the nation's economy. In other words, that the government policy regarding minimum wages, which had wanted to protect labor exploitation, if not implemented properly, would adversely affect the economic development of thecommunity.